Bottom-up field-directed self-assembly of magnetic nanoparticles into ordered nano- and macrostructures. (19th February 2021) - Preger, Calle; Josefsson, Martin; Westerström, Rasmus; Messing, Maria E
Abstract: Directed self-assembly of nanoparticles (NPs) is a promising strategy for bottom-up fabrication of nanostructured materials with tailored composition and morphology. Here, we present a simple and highly flexible method where charged magnetic aerosolized (i.e. suspended in a gas) NPs with tunable size and composition are self-assembled into nanostructures using combined electric and magnetic fields. Size-selected Co, Ni, and Fe NPs have been generated by spark ablation, and self-assembled into different structures, ranging from one-dimensional nanochains to macroscopic three-dimensional networks. By comparing the resulting structures with simulations, we can conclude that the magnetization of the NPs governs the self-assembly through interparticle magnetic dipole−dipole interactions. We also show how the orientation of the external magnetic field directs the self-assembly into differently aligned nano- and macroscopic structures. These results demonstrate how aerosol deposition in a combined electric and magnetic field can be used for directed bottom-up self-assembly of nanostructures with specialized composition and morphology.